Holocene fringing reef along southern Andaman and Swaraj Dweep shoreline - Misra, Saikat Kumar; Menon, Shradha; Sahoo, Ramendra; Mannu, Utsav; Khanna, Pankaj (Frontiers in Marine Science, 2024)
The Andaman and Nicobar Islands are rimmed by discontinuous fringing reef that is in general wider on western margin vs the eastern margin. This study characterizes the facies updip from the modern fringing reefs to the present shoreline of south Andaman and Swaraj Dweep, and describes in detail the coral terraces/carpets within and above the inter-tidal zone representing the Holocene Fringing reef. Field studies, satellite, and drone datasets have been utilized to map different facies, that include: coralgal boundstone, biodetrital-grainstone, beachrock, and coralgal rudstone. Multiple exposed microatolls as well as coral terraces (coral carpets) of Acropora and Porites (dated 8.7-8.4 ka BP) have been identified within the intertidal zone (Radhanagar Beach, Swaraj Dweep) indicating that Holocene fringing reef have down-stepped offshore to the current location of modern fringing reefs owing to either tectonics or eustasy. The eustatic sea-level fluctuations are relatively well established for the Holocene and we compute the tectonic uplift rates utilizing the stream-power-incision and linear-inversion model. A tectonic uplift rate of 0.05 mm/yr (for Swaraj Dweep) during the past 100 ka is estimated, while taking into account a wide range of erodibility indexes and response time intervals. It is identified that the computed uplift rate is an amalgamation of the coseismic deformation along with the interseismic and aseismic surface deformation. Thus, not all exposed coral terraces/microatolls are exposed due to coseismic deformation (for example uplift in parts of Andaman due to earthquake in 2004). The average long-term uplift rates are a magnitude lower than the eustatic sea-level fall rates during Holocene, thus, we suggest that most of the Holocene fringing reefs are exposed due to eustatic sea-level fall and down-stepped to the current location of the modern fringing reefs. This would entail that the eustatic sea-level change rates would play a significant role in determining future of the modern fringing reef (catch-up vs keep up vs give up), and the coastal morphology of south Andaman and Swaraj Dweep, with implications for coastal inundation and stability in the scenario of climate change.